A new unified conceptual framework involving maintenance energy, metabolism and toxicity for research on degradation of organic pollutants. (August 2021) - Gao, Lin; Gu, Ji-Dong
Abstract: A conceptual framework considering toxicity, metabolism and maintenance energy is proposed for research on microbial degradation of organic pollutants and bioremediation. There is a specific concentration range for metabolism of a selective pollutant by microorganisms and this range is above the concentration for maintenance requirement and below one starting to show toxicity. This framework will help the enrichment of microorganisms for isolation and their metabolism successfully, and bioremediation for cleaning up efficiently. By knowing the concentrations of maintenance energy and toxicity, degradation of any pollutants can be carried out more objectively. We propose this framework with indole and its methylated derivatives as examples and also point out several of the most critically important factors involved, specifically enrichment culturing and transfer technique, culture medium and composition, the target organic pollutant as the sole source of carbon and energy, co-metabolism, and source of the potential capable of microorganisms. The challenges facing the scientific community on degradation research are about the understanding and also implementation of the most effective scientific methods to test the research hypothesis to obtain the most significantly and convincing results. With the information presented, it is hoped that this conceptual framework can improve to better design research experiments to advance new knowledge on microbial degradation and also implement bioremediation more effective in applications for cleaning up the contaminated sites.